2011
DOI: 10.5194/amtd-4-4753-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Validation of SCIAMACHY limb NO<sub>2</sub> profiles using solar occultation measurements

Abstract: The increasing amounts of reactive nitrogen in the stratosphere necessitates accurate global measurements of stratospheric nitrogen dioxide (NO2). Over the past decade, the SCIAMACHY (SCanning Imaging Absorption spectroMeter for Atmospheric CHartographY) instrument on ENVISAT (European Environmental Satellite) has been providing global coverage of stratospheric NO2 every 6 days, which is otherwise difficult to achieve with other systems (e.g. balloon measurements, solar occultation). In t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…The term "a priori" here does not mean that the ozone DIAL retrieval uses a variational/optimal estimation method (it does not), but simply means that the information comes from ancillary (i.e., non-lidar) measurements or models, and is input as "truth" in the ozone DIAL processing chain. The input quantities in this case can be of different nature, namely mixing ratio or number density (e.g., Ahmad et al, 2007;Bauer et al, 2012;Bracher et al, 2005;Brohede et al, 2007;Brühl et al, 2013;Cao et al, 2006;He et al, 2014;McLinden et al, 2014). In order to ensure self-consistency in our measurement model, input quantities independent of air number density should be chosen.…”
Section: Uncertainty Owing To Interfering Gases' Atmospheric Profilesmentioning
confidence: 99%
“…The term "a priori" here does not mean that the ozone DIAL retrieval uses a variational/optimal estimation method (it does not), but simply means that the information comes from ancillary (i.e., non-lidar) measurements or models, and is input as "truth" in the ozone DIAL processing chain. The input quantities in this case can be of different nature, namely mixing ratio or number density (e.g., Ahmad et al, 2007;Bauer et al, 2012;Bracher et al, 2005;Brohede et al, 2007;Brühl et al, 2013;Cao et al, 2006;He et al, 2014;McLinden et al, 2014). In order to ensure self-consistency in our measurement model, input quantities independent of air number density should be chosen.…”
Section: Uncertainty Owing To Interfering Gases' Atmospheric Profilesmentioning
confidence: 99%
“…(12) comprise the sum of ancillary ozone and NO 2 number densities taken at all altitudes from the ground to the altitude considered z(k). Depending on the data source, these ancillary profiles may be mixing ratio or number density (Ahmad et al, 2007;Bauer et al, 2012;Bracher et al, 2005;Brohede et al, 2007). Assuming that all values within the same ancillary profile are fully correlated, uncertainty components owing to the ancillary ozone and NO 2 profiles can be propagated to temperature similarly to the uncertainty component owing to air number density (i.e., Eq.…”
Section: Uncertainty Owing To Ancillary Ozone and No 2 Number Densitymentioning
confidence: 99%
“…Their O 3 scaling technique allowed retrieval of NO 2 concentrations of 15 ± 15 ppt in the TTL, with a range of 70-170 ppt in the mid-latitude lower stratosphere associated with older stratospheric air intrusions. However, previous studies have shown large associated uncertainties in NO 2 measurements based on remote sensing instruments, which also depends on the individual observation geometries and instrument operation times (e.g., 30 % of total relative error of NO 2 measurements below 25 km; Weidner et al, 2005 and 50 % error for satellite measurements from SAGE II bellow 25 km; Bauer et al, 2012).…”
Section: Br Y Partitioningmentioning
confidence: 99%